Capillary Microfluidic Systems for Precise Microparticle Separation - Hassani, Mohsen; Sanati Nezhad, Amir (CMBES Proceedings, 2024)
This study introduces an innovative capillary-based microfluidic system for precise microparticle separation. Fabricated with a Co2 laser, the multi-layered microfluidic allows efficient particle manipulation within microchannels. Experimental validation demonstrates high-throughput processing within two minutes, showcasing its potential for rapid diagnostics in diverse applications.